HUBUNGAN FAKTOR PERILAKU LANSIA DAN DUKUNGAN KELUARGA TERHADAP PEMANFAATAN POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS SUNGAI SEMBILAN - Nurjannah, Siti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
The increasing of elderly result impact in increased health services for the elderly, one of is integrated service post of elderly. The increasing of health care result are not offset with interesting or visiting the elderly to utilize behavioral health services. The purpose of this study was to determine the relationship of the behavior of elderly and family support against utilization the integrated service post of elderly. The study design was a cross sectional with the population of each month amounted to 70 people with an age range 57 to 90 years. The sample is done by Accidental sample totaling 59 respondents and data collection by questonnaaire. The results of research by bivariate analysis was using the chisquare test shows that there is a relationship between the knowledge of the elderly with the use of integrated service post of elderly where p value (0.000) < α 0.05, there is a relationship between attitude with the use of integrated service post of elderly where the p value(0.000) < α 0.05, there is a relationship between practice with the use of integrated service post of elderly where the p value (0.001) < α 0.05, there is a relationship between family support with the use of integrated service post of elderly where the p value (0.001) < α 0.05. Researchers hope that the Healt Center staff can improve the socialization of activity in integrated service opost for elderly, a Cadre of integrated service post and family about information, remind the schedule of integrated service post as an effort to motivate the elderly to utilize the integrated service post of elderly. It is expected for cadres of integrated service post to be able to motivate families to provide support to the elderly.